2016
DOI: 10.1017/s0954579416001073
|View full text |Cite
|
Sign up to set email alerts
|

Coping and mental health outcomes among Sierra Leonean war-affected youth: Results from a longitudinal study

Abstract: This study explored how coping with war-related traumatic events in Sierra Leone impacted mental health outcomes among 529 youth (aged 10-17 at baseline; 25% female) using longitudinal data from three time points (Time 1 in 2002, Time 2 in 2004, and Time 3 in 2008). We examined two types of coping items (approach and avoidance); used multiple regression models to test their relations with long-term mental health outcomes (internalizing behaviors, externalizing behaviors, adaptive/prosocial behaviors, and postt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 83 publications
(112 reference statements)
0
20
0
Order By: Relevance
“…The present paper focuses on issues of general concern amongst adult refugees. The reader is referred to the specialized literature on vulnerable sub‐populations (child soldiers, unaccompanied minors, children and youth, single or widowed women) and specific geographical situations around the world.…”
mentioning
confidence: 99%
“…The present paper focuses on issues of general concern amongst adult refugees. The reader is referred to the specialized literature on vulnerable sub‐populations (child soldiers, unaccompanied minors, children and youth, single or widowed women) and specific geographical situations around the world.…”
mentioning
confidence: 99%
“…Finally, the chronosystem incorporates time-based effects (e.g., generational effects). An increasing number of psychologists researching youth wellbeing in contexts of political violence have applied this framework using process-oriented and longitudinal designs, which have broadened our understanding of development to include processes within the family, school, and community settings, and to address ways that these may change across historical time (Aber et al, 2017;Cummings, Merrilees, Taylor, Goeke-Morey, & Shirlow, 2017a;Huesmann et al, 2017;Sharma, Fine, Brennan, & Betancourt, 2017).…”
mentioning
confidence: 99%
“…A growing body of research has demonstrated the adverse impacts of forced migration on mental health by showing higher rates of psychiatric disorders, particularly posttraumatic stress disorder (PTSD; Cengiz, Ergun, & Çakıcı, 2019;Hameed, Sadiq, & Din, 2018). At the same time, it has also been established that some individuals may show positive psychological adaptation in the face of forced migration (Sharma, Fine, Brennan, & Betancourt, 2017;Siriwardhana, Ali, Roberts, & Stewart, 2014;Ward & Kennedy, 1999). Some research has examined mental health among refugees, yet additional research on potential risk or protective factors that impact psychological adaptation is crucial for informing efforts to prevent PTSD and other negative mental health outcomes.…”
mentioning
confidence: 99%